Intramuscular and intradermal injection of capsaicin: a comparison of local and referred pain - Witting, Nanna; Svensson, Peter; Gottrup, Hanne; Arendt-Nielsen, Lars; Jensen, Troels S. (Pain (Amsterdam), 2000)
The present study compared capsaicin-induced muscle and skin pain in humans. Twelve healthy subjects received, in a randomised, balanced order, 3 intramuscular (i.m.) injections into the brachioradial muscle: capsaicin 100 microg/1 ml, capsaicin 100 microg/20 microl or 1 ml solvent (Tween 80), and one intradermal injection (i.d.): capsaicin 100 microg/20 microl. Local and referred pain intensities and areas were assessed from 0 to 60 min after injection. Intradermal capsaicin produced more intense local pain than i.m. capsaicin in the first min (skin: 68+/-6, muscle: 51+/-6 mm VASxmin, P<0.05). In contrast, the local pain offset was later (muscle: 38+/-5, skin: 23+/-5 min, P<0.05) and referred pain was more frequent (muscle: 9/12, skin: 1/12 subjects, P<0.01) following i.m. capsaicin compared with i.d. capsaicin. Capsaicin (1 ml) produced significantly more pain than 20 microl i.m. (pain in the first min: 1 ml: 71+/-6, 20 microl: 51+/-6 VASxmin, P<0.05, offset: 1 ml: 50+/-4, 20 microl: 38+/-5 min, P<0.05). The different local and referred pain following identical noxious stimulation of muscle and skin indicates that the neurophysiological mechanisms underlying skin and muscle pain differs. The model with identical noxious stimulation of muscle and skin may be suitable for the study of differences in deep and superficial pain as seen in the clinic.